Post-immunization leucocytosis and its implications for the management of febrile infants. Issue 20 (11th May 2018) - Prentice, Sarah; Kamushaaga, Zephyrian; Nash, Stephen B.; Elliott, Alison M.; Dockrell, Hazel M.; Cose, Stephen
Abstract: Aims: Clinical guidelines for management of infants with fever but no evident focus of infection recommend that those aged 1–3 months with a white cell count >15 × 10 9 /l have a full septic screen and be admitted for parenteral antibiotics. However, there is limited information about leucocyte changes following routine immunization, a common cause of fever. We investigated white cell counts shortly after routine immunization in Ugandan infants under 3 months of age. Methods: White cell counts were measured in 212 healthy infants following routine immunizations (DTwP-HepB-Hib, oral polio and pneumococcal conjugate 7 vaccines) received prior to 3 months of age. Results: Mean leucocyte counts increased from 9.03 × 10 9 /l (95% confidence interval 8.59–9.47 × 10 9 /l) pre-immunizations to 16.46 × 10 9 /l (15.4–17.52 × 10 9 /l) at one-day post-immunizations at 6 weeks of age, and 15.21 × 10 9 /l (14.07–16.36 × 10 9 /l) at one-day post-immunizations at 10 weeks of age. The leucocytosis was primarily a neutrophilia, with neutrophil percentages one-day post-immunization of 49% at 6 weeks of age and 46% at 10 weeks of age. White cell parameters returned to baseline by two-days post-immunization. No participant received antibiotics when presenting with isolated fever post-immunization and all remained well at follow-up. Conclusions: In our study almost half the children <3 months old presenting with fever but no evident focus of infection at one-day post-immunization met commonly used criteria for full septic screen and admission for parenteral antibiotics, despite having no serious bacterial infection. These findings add to the growing body of literature that questions the utility of white blood cell measurement in identification of young infants at risk of serious bacterial infections, particularly in the context of recent immunizations, and suggest that further exploration of the effect of different immunization regimes on white cell counts is needed. This observational work was nested within a clinical trial, registration number ISRCTN59683017.